Historic Time Perception in Primary Classes: Educational Expectations and Achievements - Žemgulienė, Aušra (Acta Paedagogica Vilnensia, 2020)
History teaching has been raising many didactic issues recently. First, the concept of the very discipline of history has been undergoing changes; the aim of school education is being shifted from memorizing pre-defined content toward developing historical literacy based on critical thinking and the development of historical research skills. Second, admitting the impact of the sociocultural context on pupil achievement, the attitude toward children’s receptive skills and their development has been gaining new perspectives. This is of high importance in primary education, where a heroic story is often still dominant. At present, the discourse of primary education curriculum change emphasizes the attractive communication of scientific knowledge and the demand for active research to broaden children’s deep understanding. However, the development of historical literacy in primary classes still remains to be complicated, since, on the one hand, it requires new landmarks – what and how to teach, and on the other hand, research in this field has been very limited.In Lithuania, there is an intention to re-new the curricula in all the fields. Therefore, it becomes relevant to analyze what skills to understand historical time should be developed in primary classes. This scientific problem is solved by carrying out a qualitative analysis of the content of the primary education curriculum. Based on the chosen model of understanding historical time (De Groot-Reuvekamp, Ros, Van Boxtel, Oort 2015), this article analyzes the extent to which the curriculum requirements of history teaching correspond to the goals and comprehension levels of the model (A – Emergent; B – Initial; C – Continued) and what should be improved when updating the curriculum. The last stage of research contains the research data supplemented with data gathered by a survey of the primary teachers and prospective primary teachers, who are in the final year of their Childhood Pedagogy university studies. The respondents defined, in written form, their expectations regarding the skills of historic time perception, which should be developed so that primary school students would understand what historic time is.The research results reveal that the present curriculum requirements for the primary school pupils are low. They lead toward the stage of acquiring understanding (A – Emergent) rather than Initial (B) or Continued (C) stages. Descriptions of program knowledge, understanding, and procedural skills do not reflect growth-oriented expectations and research-based learning outcomes. The analysis of results have shown that their expectations do not correspond to the conclusions made by the latest academic research about the primary age student learning achievement possibilities. The study revealed that teachers’ and students’ express higher expectations for student achievement than the program. Therefore, while revisiting the curriculum, it is important to pay more attention to the development of historical research and higher thinking skills, which would be a significant step toward gaining a deeper understanding of historic time.
Keywords: understanding of historical time; history teaching in primary classes; curriculum